2018
DOI: 10.1002/mnfr.201700531
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of 27‐Hydroxycholesterol Induced by Dietary Cholesterol in Brain Contribute to Learning and Memory Impairment in Rats

Abstract: This study indicates that the mechanisms of dietary cholesterol on learning and memory impairment may be involved in cholesterol metabolism and lysosome function with the increase of plasma 27-OHC, thus resulting in Aβ formation and accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Our recent studies showed the toxic effect of 27-OHC in C6 glioma cells and in the brains of Sprague-Dawley rats fed a high-cholesterol diet. Our results suggest that 27-OHC may be able to inhibit cholesterol synthesis in the brain Zhang et al, 2018). In addition to being involved in cholesterol metabolism, 27-OHC is also involved in the inflammatory process.…”
mentioning
confidence: 69%
“…Our recent studies showed the toxic effect of 27-OHC in C6 glioma cells and in the brains of Sprague-Dawley rats fed a high-cholesterol diet. Our results suggest that 27-OHC may be able to inhibit cholesterol synthesis in the brain Zhang et al, 2018). In addition to being involved in cholesterol metabolism, 27-OHC is also involved in the inflammatory process.…”
mentioning
confidence: 69%
“…In this case, production, transport and elimination of Aβ may play key roles in Aβ pathology of MCI patients. While several studies including ours have manifested that the accumulation of Aβ in brain may be associated with the disturbance of 27‐OHC in brain and/or circulation , the underling mechanisms in the correlation between oxysterols and Aβ are still unclear. The second aim of this study is to investigate the molecular mechanism of excessive oxysterols on regulating Aβ metabolism.…”
Section: Introductionmentioning
confidence: 86%
“…The reactions were under the following conditions: 95°C for 10 minutes, 40 cycles of 95°C for 10 s, 60°C for 20 s and 72°C for 10 s. RNU6B was used as the internal standard. For gene expression analysis, 1 μg total RNA was used as template to synthesize cDNA and further subjected to qRT‐PCR reaction as described elsewhere . GAPDH served as an internal reference for normalization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations